2000
DOI: 10.1159/000026666
|View full text |Cite
|
Sign up to set email alerts
|

Human Research on MDMA (3,4-Methylene- dioxymethamphetamine) Neurotoxicity: Cognitive and Behavioural Indices of Change

Abstract: Laboratory animals can develop serotonergic neurotoxicity after repeated doses of 3,4-methylenedioxymethamphetamine (MDMA) or ‘Ecstasy’. If similar neural damage occurs in humans, this may be evident in cognitive or behavioural impairments. In a review of the behavioural skills shown by drug-free recreational Ecstasy users, three aspects of cognitive performance are often affected: reduced memory for new information (Rivermead Behavioral Memory, supraspan word recall), impaired higher executive processing (Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
97
0
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 22 publications
10
97
0
9
Order By: Relevance
“…Studies of MDMA users report no effect, increases, or decreases in selfperceptions of anxiety (Liester et al 1992;Morgan 1998;Parrott 2000;Verkes et al 2001;Wareing et al 2000). These diverse results suggest that MDMA influences on anxiety levels are likely dependent upon the total exposure to MDMA, the time of abstinence from the drug, use of other drugs, and the type of anxiety assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of MDMA users report no effect, increases, or decreases in selfperceptions of anxiety (Liester et al 1992;Morgan 1998;Parrott 2000;Verkes et al 2001;Wareing et al 2000). These diverse results suggest that MDMA influences on anxiety levels are likely dependent upon the total exposure to MDMA, the time of abstinence from the drug, use of other drugs, and the type of anxiety assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Some human MDMA users have also reported increased levels of anxiety that can persist even after periods of abstinence from the drug (Gamma et al 2000;Parrott 2000;Verkes et al 2001;Wareing et al 2000). Animals treated with brief, high-dose regimens also exhibit persistent increases in anxiety-like behaviors, even without long-term serotonin depletion (Clemens et al 2004;Fone et al 2002;Gurtman et al 2002;McGregor et al 2003).…”
mentioning
confidence: 99%
“…Studies that have examined the effect of MDMA on impulsivity in abstinent MDMA users have provided conflicting results. McCann et al (1994) reported a decrement in impulsivity ratings of MDMA users as measured by the Multidimensional Personality Questionnaire, whereas others reported elevated scores of impulsivity in heavy MDMA users, using different subjective measures of impulsivity (Butler and Montgomery, 2004;Morgan, 1998Morgan, , 2000Parrott, 2000). Elevated levels of impulsiveness have been associated with lower levels of 5HT and CSF-5HIA (Linnoila et al, 1983(Linnoila et al, , 1993 and with dopaminergic activation in the prefrontal cortex leading to a reduction in 'inhibitory control' over behavioral functions (Jentsch and Taylor, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the popular recreational drug ecstasy (3,4-methelenedioxymethamphetamine, MDMA) causes damage to the 5-HT axons both in animals (eg Hatzidimitriou et al, 1999;Ricaurte et al, 2000) and humans (Gerra et al, 1998;Kish et al, 2000). The use of ecstasy is associated with decreased memory function and increased symptoms of depression (Parrott, 2000;Verbaten, 2003; Thomasius et al, 2003).…”
Section: Introductionmentioning
confidence: 99%